Determinant Factors for Delays in Settlement of Gono-Gini Asset Disputes - Lukum, Silvani Nur Rahmat; Junus, Nirwan; Kamba, Sri Nanang Meiske (Damhil Law Journal, 2022)
This article discusses the highest factors that hinder the resolution of disputes over mixed assets. The determinant factors that impede the implementation of the religious court's decision on the resolution of disputes over arbitrary assets in the City of Gorontalo to those who apply for the separation of arbitrary assets are internal and external factors. Internal factors include obstacles; the lack of human resources for judges at court, as well as the knowledge of judges in resolving cases where the wife who is more dominantly working earns income while the husband does not work. In this case the judge uses the principle of justice by determining that the ex-wife gets Â¾ of the share while the ex-husband gets Â¼ of the share. External factors include: Partners between ex-husbands and ex-wives are not willing, do not accept, or do not agree with the results of the decision from the court. The approach used in writing this article is empirical juridical with a case study approach. Based on the data found in this article, the highest factor in the delay in resolving disputes over Gono-Gini assets is disagreement between ex-husbands and ex-wives over the decision of the Class IA Gorontalo Religious Court.